Synthesis and scaled-up of non-active and active Belite-Alite-Ye'elimite clinker (BAY) - Zea-Garcia, Jesus D.; García-Aranda, Miguel Ángel; Gómez-de-la-Torre, María de los Ángeles; Santacruz-Cruz, María Isabel (My University, 2017)
Ordinary Portland cement (OPC) is an environmentally contentious material, as for every ton of OPC produced, ~0.97 tons of CO2 are released. This opens the need of designing new formulations of cements formed by low calcite demanding phases, such as ye'elimite, that release less CO2 during their fabrication. Belite-Alite-Ye’elimite (BAY) cements are promising eco-friendly building materials as OPC substitutes at a large scale[1]. There action of alite and ye´elimite with water should develop cements with high mechanical strengths at early ages,while belite will contribute to later curing times. However, they develop lower mechanical strengths at early-medium ages than OPC[2]. It is known that the presence of different polymorphs of belite and ye'elimite affects the hydration due to the different reactivity of those phases[3]. The aim of this work is to process, characterize and scaled-up a non-active (with coexisting alite,β-belite and ye'elimite) and an active(with coexisting alite,α'H-belite and ye'elimite) BAY clinkers prepared with CaF2 and ZnO, named here after BAY-Z and a-BAY-Z respectively, to develop, in a future step,comparable mechanical strengths to OPC. The parameters evolved in the preparation of the clinker shave been optimized, such as these lection of raw materials (including mineralizers and activators), clinkering conditions and scaled-up methodology. Finally, the clinker was characterized through laboratory X-ray powder diffraction in combination with the Rietveld methodology. Cement nomenclature: C=CaO, S=SiO2, A=Al2O3, s=SO3, C2S= belite, C3S= alite, C4A3s=ye’elimite, C4AF=ferrite, C3A=tricalciumaluminate, Cs=anhydrite.
This Discussion Meeting of the EuCheMS Division of Solid State and Materials Chemistry is focused on the latest developments in synthesis, properties, and structural investigations of solids. The meeting has been held just before the 6th EuCheMS Congress, 11-15 September (euchemsseville2016. eu/).
Keywords: Cemento; Cemento Portland; Belite-Alite-Ye'elimite clinker; Synthesis; X-Ray Diffraction